Knowledge and Practice of Health Care Providers Regarding Syndromic Management of Sexually Transmitted Infections in Primary And Secondary Health Care Facilities - Saha, Pretom; Sarmin, Rubaiyath; Alam, Ummul Khair; Dastider, Sathi (Journal of Preventive and Social Medicine, 2025)
Introduction: Sexually transmitted infections (STIs) remain a global health concern, necessitating effective management to mitigate complications and transmission. This study focuses on the syndromic approach, employing clinical syndromes for STI diagnosis and treatment, particularly in the context of primary and secondary healthcare facilities in Bangladesh. This research aimed to assess the knowledge and practice of healthcare providers concerning the syndromic management of STIs in Bangladesh. Specific objectives included evaluating knowledge levels, current practices, healthcare facility services, and associated factors. Methods: A cross-sectional study was conducted from January 2023 to December 2023 in Upazila Health Complexes and District Hospital of Noakhali District. Data were collected from 62 healthcare providers through face-to-face interviews, utilizing a pretested semi-structured questionnaire and the District STD Quality of Care Assessment (DISCA) tool. Results: The demographics of physicians showed varying levels of experience and educational backgrounds. While 59.7% were aware of the national guidelines for STI management, knowledge gaps were observed in specific treatment scenarios. For instance, 83.9% correctly acknowledged the treatment of urethral discharge for Gonorrhea, while only 24.2% accurately specified the complete regimen, encompassing the correct drug, dose, frequency, and duration. Assessing STI management practices, the study found that 54.8% of healthcare providers had encountered patients with STI symptoms. Among this group, 44.11% demonstrated correct adherence to treatment protocols, prescribing the accurate drug, dose, frequency, and duration. Notably, 64.5% of STI patients received counseling sessions on a regular basis. However, the study also revealed common obstacles, such as issues with patient non-compliance, privacy concerns, and social stigmas that affect the availability of STI treatment. Accessibility data regarding the services provided by healthcare facilities revealed that 88.9% of facilities reported challenges protecting privacy for patients. Conclusion: Healthcare providers demonstrated varying levels of knowledge and practice in syndromic STI management. Identified gaps suggest a need for targeted training programs and interventions to enhance provider skills. The study underscores the importance of addressing systemic challenges in STI care provision, including privacy concerns and social stigmas, to improve overall healthcare outcomes. JOPSOM 2024; 43(2): 44-52